Czy istnieje jeszcze tabu? Kilka refleksji na temat prozy polskiej po roku 1989 - Pięta, Iwona (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2014)
Is there a taboo any more? Some reflections on Polish fiction after 1989 This paper aims at answering the questions about the nature of relations between social standards and issues put forward by the writers, who made their debuts after 1989. It shows how and why the concept of taboo has been changing in Polish culture in the last two decades, and what reasons can one indicate for writers’ transgressions of moral and cultural standards so far regarded inviolable.